Remote visualization on medical datasets over thin clients with support of grid environment - Ahmed, Aboamama A.; Abd. Latiff, Muhammad Shafie; Abu Bakar, Kamalrulnizam (2006)
Existing grid enabled data visualization and remote distributed visualization are often take the direction of remote viewing and zooming techniques of remotely processed datasets. However the continuous increase in the size of datasets and visualization operation causes insufficient performance with traditional desktop computers. Additionally, the visualization techniques such as Isosurface is depend on the available resources of the running machine and the size of datasets. Moreover, the continuous demand for powerful computing powers and continuous increase in the size of datasets results an argent need for a grid computing infrastructure. However, some issues raises with current grid such as resources availability at the client machines which are not sufficient enough to process large datasets. Additionally, different output devices and different network bandwidths between the visualization pipeline components often results output suitable for one machine and not suitable for another. This paper focuses and investigates the visualization of medical datasets on thin client devices with support of grid computing